Perbandingan Wadah Keranjang Buah Kelapa Sawit dengan Jerigen untuk Mengurangi Sampah yang Terbawa ke Pabrik Kelapa Sawit - Toto Suryanto; Handika Muhammad Al Faris (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
This research aims to determine the percentage of waste carried using a fruit basket and jerigen, and get a comparison of work performance using jerigen and brondolan basket containers. The study was conducted at PT Wahana Plantation and Product located in Sona Village, Gandis District, Sintang Regency, West Kalimantan on March 29 to April 6 2019. This research used the direct application method and field observations. The results showed that the percentage of waste in fruit basket containers was smaller (4.8%) than jerigen (6.3%). Work performance obtained from the fruit basket container was higher (0.93 hk/ha) compared to jerigen (0.70 hk/ha).